Influence of Top Layer Composition on the Photovoltaic Parameters of P3HT:PCBM Organic Solar Cells - Muhammet Erkan Köse (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Spin and spraydeposition techniques have been used sequentially to examine the effect of thecomposition of top blend layer on the photovoltaic properties of organic solarcells using well-known poly(3-hexylthiophene):[6,6]-Phenyl C61 butyric acidmethyl ester (P3HT:PCBM) blend. Devices were prepared by spraying an extralayer of P3HT or PCBM (~15 nm) onto spin coated (1:1) blend film. P3HT-rich topphase slightly perturbs photovoltaic activity whereas PCBM-rich top phasedrastically changes the power conversion efficiencies with a marked decrease infill factors. Carrier mobilities were only marginally affected by the presenceof spray coated top layers. However, series resistance of top phase P3HT-richblends remained the same with respect to spin coated sample whereas top phasePCBM-rich blends exhibit relatively higher series resistances for both annealedand non-annealed samples. Based on the presented results, one might speculatethat electron injection to cathode with P3HT is almost as efficient as withPCBM for active layers utilizing P3HT:PCBM blend.